2007
DOI: 10.3892/or.17.2.329
|View full text |Cite
|
Sign up to set email alerts
|

Immortalized ovarian surface epithelial cells acquire tumorigenicity by Acrogranin gene overexpression

Abstract: Malignant transformation is caused by multi-step genetic mutations, and growth factors are believed to play important roles in developing and maintaining malignant phenotype. However, there is no direct evidence that a specific growth factor contributes to malignant transformation of phenotypically normal cells. In order to assess the function of Acrogranin (also known as granulin epithelial precursor; GEP) in ovarian carcinogenesis, ovarian surface epithelial (OSE) cells, which are supposed to be the origin o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 19 publications
1
21
0
1
Order By: Relevance
“…Progranulin has been reported to activate many of the typical cell proliferation signaling pathways, including ERK, PI3K, and Akt pathways (48,50,51), not only in tumor cells but also in neurons (52,53). Progranulin may be a prognostic marker (54) or a therapeutic target in cancer: progranulin overexpression confers an aggressive phenotype to adenocarcinoma (46), immortalized ovarian epithelial cells (55), breast cancer (49,56), and hepatocellular carcinoma (57), and anti-progranulin treatment reduces in vivo tumorigenicity of teratoma (58) and breast cancer cell lines (59). However, it should be emphasized that although these early studies strongly linked progranulin to cancer, no cell surface receptor has been shown to mediate these effects.…”
Section: What Does Progranulin Do?mentioning
confidence: 99%
“…Progranulin has been reported to activate many of the typical cell proliferation signaling pathways, including ERK, PI3K, and Akt pathways (48,50,51), not only in tumor cells but also in neurons (52,53). Progranulin may be a prognostic marker (54) or a therapeutic target in cancer: progranulin overexpression confers an aggressive phenotype to adenocarcinoma (46), immortalized ovarian epithelial cells (55), breast cancer (49,56), and hepatocellular carcinoma (57), and anti-progranulin treatment reduces in vivo tumorigenicity of teratoma (58) and breast cancer cell lines (59). However, it should be emphasized that although these early studies strongly linked progranulin to cancer, no cell surface receptor has been shown to mediate these effects.…”
Section: What Does Progranulin Do?mentioning
confidence: 99%
“…The potency of PGRN as a tumorigenic agent was demonstrated using primary human cells from ovarian epithelia (20) and uterine smooth muscle. (12) Human primary cells are difficult to transform by gene transfer in culture, (85) requiring at minimum the increased expression of telomerase activity, blockade of the retinoblastoma (Rb) tumor suppressor system, and a strong mitotic drive provided in most experiments by oncogenes such as mutant RAS.…”
Section: Progranulin In Cancermentioning
confidence: 99%
“…PGRN can substitute for RAS in the transformation process. The combination of telomerase (Tert) and SV40 T-antigen (to block the Rb and P53 tumor suppressors) immortalized, but did not transform primary human ovarian cells (20) or uterine smooth muscle cells, (12) but when GRN was included with Tert and SV40, the primary cells became very tumorigenic in mice. (12,20) It is interesting to speculate whether this is related to the unusual property of PGRN as a conjoint competence and progression factor, although at present experimental evidence neither supports nor refutes this hypothesis.…”
Section: Progranulin In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Epithelial GRN expression has been associated previously with advanced invasive cancers (9,10). In previous reports in mice, depleting GRN from cancer cells by mRNA targeting (11) or monoclonal antibody strategies (12) reduced their tumorigenicity, while overexpressing GRN in cells that are only weakly tumorigenic enhanced their malignant properties (13,14). Taken together, these data suggest a model in which GRN delivered to a tumor by GRN + Sca1 + cKit -CD45 + BMCs plays a key role in the early stages of tumor development, particularly in stromal formation (7), but as tumors progress, GRN expression is no longer restricted to these cells (7), as cancer epithelial cells acquire the ability to both express and respond to GRN.…”
Section: Progranulin In Human Breast Cancersmentioning
confidence: 99%